Aplicação de modelos de quebra de partículas do ambiente de simulação do método dos elementos discretos no estudo de microprocessos de cominuição - Jiménez-Herrera, Narcés (2017)
In this work one of the comminution microprocesses were studied using three particle breakage models within the DEM simulation environment: The Bonded Particle Model – BPM, the Fast Breakage Model - FBM, and the Particle Replacement Model – PRM. Such models were calibrated on the basis of the median fracture energy of individual particles. The potential of these tools to describe comminution was demonstrated through validation using virtual experiments of impact breakage of unconfined particle beds. They showed that the BPM presents higher resolution in the description of effects as the broken mass and particle capture radius on the bed. However, the poor adherence between experimental and simulated product size distribution suggest the need to improve the model to obtain a better representation of this effect. The PRM demonstrated some potential in the description of broken mass and particle capture, and higher adherence between experimental and simulated product size distribution. The FBM demonstrated potential in the description of both the breakage probability and the t10 parameter of particles, but in a non-simultaneous way. The latter also demonstrated some potential in the description of broken mass and particle capture, and poor resolution in the description of experimental product size distributions.